Uniqueness of the entanglement measure for bipartite pure states and thermodynamics. - Vedral, V; Kashefi, E (2002)
We apply the axiomatic approach to thermodynamics presented by Giles to derive a unique measure of entanglement for bipartite pure states. This implies that local manipulations of entanglement in quantum information theory and adiabatic transformations of states in thermodynamics have the same underlying mathematical structure. We discuss possible extensions of our results to mixed and multipartite states.